The Effectiveness of the Dhuha Prayer Habituation Program in Improving Student Discipline - Ayu Rahma Ramadani; Ade Ismatullah; Ahmad Yani (Penerbit Hellow Pustaka, 2026)
This study addresses the problem of a gap between the objectives of the Dhuha Prayer Habituation Program and the persistent disciplinary issues among students at MA Nagrak Madani Sukabumi. Its purpose is to analyze the program's implementation, effectiveness in shaping student discipline, and the supporting and inhibiting factors. Employing a qualitative approach with a single instrumental case study method, data were collected through participatory observation, in-depth interviews, and documentation. The results show that the program is systematically implemented through a multidimensional strategy integrating regulatory, motivational, and habituation approaches, with institutional commitment and teacher role modeling as key supports. The program significantly improved students' time management, personal responsibility, and learning readiness, though challenges like facility limitations and uneven intrinsic motivation remain. It is concluded that structured worship habituation is an effective mechanism for internalizing disciplinary character. The study implies that successful character-building programs require a holistic design attentive to local ecological and psychological contexts.